Cryotolerance in Norway spruce and its association with growth rates, anatomical features and polyamines of embryogenic cultures - Vondráková, Zuzana; Cvikrová, Milena; Eliásová, Katerina; Martincová, Olga; Vágner, Martin (Tree physiology, 2010)
Our study focused on the possible association between the cryotolerance of Norway spruce (Picea abies (L.) Karst.) embryogenic cultures and the anatomical structures of their embryogenic suspensor mass (ESM), their growth rate and their content of endogenous polyamines (PAs). The anatomical characteristics and PA content during cryopreservation and regrowth were studied in the ESMs of AFO 541 and C110 cultures, which have comparable ESM anatomy but diverse growth rates, PA content and regeneration abilities after cryopreservation. Different levels of tolerance to exogenous treatment were already apparent after transfer of the ESMs to liquid media. The endogenous free PAs were maintained at high levels, with spermidine being the predominant PA in the ESM of AFO 541, while in the ESM of C110 the content of putrescine and spermidine was almost identical and rather low, the content of spermidine being approximately one-third that in the ESM of AFO 541. Osmotic pretreatment, using a double application of sorbitol followed by an application of dimethyl sulfoxide (DMSO) resulted in the continual disintegration of polyembryogenic centers and suspensors in both cell lines. A continual decrease in the level of PAs was observed during the cell osmotic pretreatment. The cells that retained their viability and regrowth ability after cryopreservation were the meristematic cells inside the embryonal heads and the cells in the intermediate area between suspensor and meristems. Restoration of AFO 541 growth after cryopreservation was almost immediate; however, the C110 ESM culture regrew with difficulty, often exhibiting callogenesis. High levels of PA-soluble conjugates and an increase in the amount of PAs bound to high-molecular-mass substances was observed in cells of AFO 541 on Day 6 after thawing and also to some extent on Day 11. On Day 21 after thawing, the amount of free putrescine and spermidine in the AFO 541 cells reached the level observed in the suspension culture before the cryotreatment. The extremely low level of PAs determined in the ESM of C110 3 weeks after thawing agreed with the cell viability and rate of regrowth observed in this culture. The possible role of PAs in the process of cryopreservation of Norway spruce cultures is discussed.
Keywords: kryoprezervace; buněčné linie; studené klima; dimethylsulfoxid; polyaminy; sorbitol; Picea; Seeds; zmrazování; smrk; Cell Line; Cold Climate; Cryopreservation; Sorbitol; Dimethyl Sulfoxide; semena rostlinná; Freezing; Polyamines